2022
DOI: 10.12681/jhvms.27885
|View full text |Cite
|
Sign up to set email alerts
|

Effect of udder type on udder traits, milk yield and some physicochemical characteristics of milk in Awassi ewes

Abstract: In this study, it was aimed to determine the effects of udder type on milk yield, udder and teat traits, and some physicochemical properties of milk in 54 Awassi ewe aged 3-4 years. In this study, Type-3 udder, which was reported to be prevalent in breeded Awassi ewes. Type-4, Type-5, and Type-6 udders were not detected in ewes. The lactation period, lactation, and the daily average milk yield values were calculated as 208.33 days, 138.59 liters, and 659.49 ml, respectively. The 90th day of lactation measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
5

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 17 publications
1
4
5
Order By: Relevance
“…In the current study, the calculated fat was found to be lower but the lactose was higher than the values reported by Şeker et al [8], Kahraman and Yüceer Özkul [15], Panayotov et al [18], Çelik and Özdemir [23] and also Tarazona et al [24]. Protein was found to be lower than the values reported by Kahraman and Yüceer Özkul [15], Panayotov et al [18], Çelik and Özdemir [23] and also Tarazona et al [24] but rate was to be higher than the value reported by Şeker et al [8].…”
Section: Physicochemical Properties Of Milkcontrasting
confidence: 87%
See 2 more Smart Citations
“…In the current study, the calculated fat was found to be lower but the lactose was higher than the values reported by Şeker et al [8], Kahraman and Yüceer Özkul [15], Panayotov et al [18], Çelik and Özdemir [23] and also Tarazona et al [24]. Protein was found to be lower than the values reported by Kahraman and Yüceer Özkul [15], Panayotov et al [18], Çelik and Özdemir [23] and also Tarazona et al [24] but rate was to be higher than the value reported by Şeker et al [8].…”
Section: Physicochemical Properties Of Milkcontrasting
confidence: 87%
“…The lactation periods of ewes were calculated according to Berger and Thomas [7]. Fat (%), solid non-fat (%), density (g•ml -1 ), lactose (%), mineral (%), protein (%), conductivity (mS•cm -1 ), and freezing point (°C) analyses of milk were measured by analyzer (Lactoscan MCCWS 3080, Milkotronic LTD, Bulgaria) in the morning and evening milking on the 30th day of lactation [8]. Measurements of the udder and teat before morning milking on the 30th day of lactation were made according to De La Fuente and Türkyılmaz [9] (FIG.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have been conducted on the Awassi breed examining the udder and teat characteristics and the relationships between them and the milk yield in particular [1,2,7,11,12,13,14,15]. However, similar studies on Bafra sheep [9,16] are observed to be insufficient and not widespread.…”
Section: Introductionmentioning
confidence: 99%
“…In order to improve udder morphology and milkability, it is recommended to use linear udder traits in practice. The relationship of udder traits with milk yield in sheep has been investigated in many studies (Dzidic et al, 2004;Kominakis et al, 2009;Mioč et al, 2009;Prpic et al, 2013;Vrdoljak et al, 2020;Seker et al, 2022;Tolu and Yazgan, 2022;Marshall et al, 2023;Smith et al, 2023). Kaygisiz and Dag (2017) found generally positive and significant correlations between udder size and type of udder and milk yield.…”
Section: Introductionmentioning
confidence: 99%